1976
DOI: 10.1111/j.1471-4159.1976.tb07014.x
|View full text |Cite
|
Sign up to set email alerts
|

DECREASE OF HOMOVANILLIC, DIHYDROXYPHENYLACETIC ACID AND CYCLIC‐ADENOSINE‐3′,5′‐MONOPHOSPHATE CONTENT IN THE RAT CAUDATE NUCLEUS INDUCED BY THE ACUTE ADMINISTRATION OF AN AMINOACID MIXTURE LACKING TYROSINE AND PHENYLALANINE1

Abstract: The oral administration of an aminoacid mixture lacking tyrosine and phenylalanine induces, in rats, a profound depletion of tyrosine in serum and in brain. Brain tyrosine is maximally depleted by 73%, 2 h after treatment, when there is a concomitant decrease in the levels of HVA (by 50%), DOPAC (by 30%) and c‐AMP (by 28%) in the basal ganglia. However, 4 to 8 h after treatment, when brain tyrosine is still depleted by 47 and 28%, respectively, DA metabolites and c‐AMP levels have returned to normal. Our findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 19 publications
3
35
0
Order By: Relevance
“…If TYR depletion lowers brain DA function, it is presumably due to decreased availability of the catcholamine precursors TYR and PHE for brain DA synthesis (Biggio et al, 1976;Moja et al, 1996). Indeed in a recent PET imaging of TYR depletion, we found that the increase in D 2 receptor binding as measured by [ 11 C]raclopride correlated significantly with the fall in the plasma ratio of TYR and PHE to large neutral amino acids (Montgomery et al, 2003).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…If TYR depletion lowers brain DA function, it is presumably due to decreased availability of the catcholamine precursors TYR and PHE for brain DA synthesis (Biggio et al, 1976;Moja et al, 1996). Indeed in a recent PET imaging of TYR depletion, we found that the increase in D 2 receptor binding as measured by [ 11 C]raclopride correlated significantly with the fall in the plasma ratio of TYR and PHE to large neutral amino acids (Montgomery et al, 2003).…”
Section: Discussionmentioning
confidence: 52%
“…TYR is a naturally occurring amino acid from which DA, and also noradrenaline, are synthesized. Administration of an amino-acid mixture free of TYR, and of the TYR precursor, PHE, lowers plasma TYR and prevents TYR brain entry by competition at the bloodbrain barrier (Biggio et al, 1976;Moja et al, 1996;Sheehan et al, 1996). The result is a marked lowering in the plasma ratio of TYR and PHE to neutral amino acids, which leads to a reduction in the availability of TYR for brain catecholamine synthesis (Fernstrom and Fernstrom, 1995;McTavish et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have used mixtures of 2-12 amino acids (Biggio et al, 1976;Fernstrom and Fernstrom 1995;McTavish et al, 1999b). Here, single or small numbers of BCAAs were used with the expectation that they would lower brain tyrosine by simple competition at the LAT-1 transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies support this possibility. APTD decreases post-mortem tissue concentrations of the dopamine (DA) metabolites homovanillic acid (HVA) and dihydroxyphenylacetic acid (Biggio et al, 1976), amphetamine-induced DA release (McTavish et al, 1999a), and cerebrospinal fluid (CSF) concentrations of HVA and the norepinephrine (NE) metabolite, 3-methoxy-4-hydroxyphenethyleneglycol (Palmour et al, 1998). In humans, though, the evidence remains circumstantial: APTD is reported to decrease blood pressure (Moja et al, 1996) and increase circulating levels of prolactin ), but direct evidence of decreased catecholamine transmission in brain is lacking.…”
Section: Introductionmentioning
confidence: 99%